Chest Imaging in the Diagnosis and Management of Pulmonary Tuberculosis: The Complementary Role of Thoraci Ultrasound - Rea, Gaetano; Sperandeo, Marco; Lieto, Roberta; Bocchino, Marialuisa; Quarato, Carla Maria Irene; Feragalli, Beatrice; Valente, Tullio; Scioscia, Giulia; Giuffreda, Ernesto; Foschino Barbaro, Maria Pia; Lacedonia, Donato (Frontiers in Medicine, 2021)
Tuberculosis (TB) is a severe infectious disease that still represents a major cause of mortality and morbidity worldwide. For these reasons, clinicians and radiologists should use all the available diagnostic tools in the assessment of the disease in order to provide precise indications about starting an anti-tubercular treatment and reduce risk of TB transmission and complications especially in developing countries where the disease is still endemic. As TB mycobacteria are mainly transmitted through respiratory droplets, the pulmonary parenchyma is usually the first site of infection. As a result, chest imaging plays a central role in the diagnostic process. Thoracic ultrasound (TUS) is a portable, non-invasive, radiation-free, and cost-contained technology which could be easily available in resource-limited settings. This perspective article focuses on the potential role of TUS in the diagnosis and management of patients with pulmonary TB. Unfortunately, there are still insufficient evidence and too contrasting data to judge TUS as an appropriate diagnostic method for the screening of the disease. Despite this, TUS may have a useful role in identifying pleural and anterior pericardial effusions or in the identification of abscesses of the anterior chest wall and paraspinal collections in low- and middle-income settings. In addition, TUS seems to have a milestone role in guiding minimally invasive interventional procedures, such as placement of chest tubes, drainage of loculated collections, thoracentesis and pericardiocentesis, and percutaneous biopsy of subpleural pulmonary consolidations or pleural plaques.